Relevansi pendidikan agama dalam menumbuhkan kesadaran berwawasan ilmu pengetahuan - Salsabilla, Putri Yulia (Maliki Interdisciplinary Journal, 2024)
This article discusses the relevance of religious education in growing knowledge-minded awareness in the modern era. Religious education is considered important in shaping a person's attitudes and behavior, but is often seen as irrelevant to the increasingly advanced developments in science and technology. This article argues that truly relevant religious education must be able to provide an understanding of the principles of science and technology, so that students not only have a strong understanding of religion, but are also able to apply it in everyday life. In this article, the author discusses several examples of religious education practices that are relevant to science, such as studying scientific concepts in the Qur'an and hadith, and studying how religious values ​​can be applied in the context of science and technology. Apart from that, the writer also discusses the importance of introducing students to a broader understanding of religion and spirituality, so that they can understand that religion and science do not have to conflict with each other. In conclusion, this article emphasizes that religious education that is relevant to science can help foster scientific awareness among students. Therefore, the right approach is needed in integrating religious education with science, and the role of religious teachers is very important in facilitating effective and relevant learning.